2004
DOI: 10.1111/j.1348-0421.2004.tb03545.x
|View full text |Cite
|
Sign up to set email alerts
|

New World Relapsing Fever Borrelia Found in Ornithodoros porcinus Ticks in Central Tanzania

Abstract: Tick-borne relapsing fever (TBRF) is found in Africa, Europe, western Asia, and North America (2). The disease is caused by several species of relapsing fever borreliae and is transmitted by various species of Ornithodoros and Argas ticks (15). Specific relationships often exist between Borrelia species and vector tick species, and certain Borrelia species are reported to be transmitted by a single tick species (18). Ornithodoros moubata complex ticks, such as O. moubata and Ornithodoros porcinus, are distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 18 publications
1
40
0
1
Order By: Relevance
“…crocidurae ; and c) a further group containing unique amplicons from ticks collected in Tanzania. This last group was distinct in its IGS sequence and is likely compatible with the novel Borrelia species from this region ( 3 , 4 , 20 ). Three sequence types were identified that clustered within this novel IGS sequence clade, separate from the B .…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…crocidurae ; and c) a further group containing unique amplicons from ticks collected in Tanzania. This last group was distinct in its IGS sequence and is likely compatible with the novel Borrelia species from this region ( 3 , 4 , 20 ). Three sequence types were identified that clustered within this novel IGS sequence clade, separate from the B .…”
Section: Discussionmentioning
confidence: 63%
“…hermsii and B . turicatae , rather than Old World tickborne relapsing fever and louseborne relapsing fever isolates ( 3 , 4 , 20 ). Insufficient material remained to allow repeat analysis for either flaB or rrs genes to confirm that Borrelia species types 1–3 were indeed the same spirochete described above.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…in Africa that strongly resemble New World relapsing fever species suggests greater globalization of these spirochetes ( 22 – 24 ). As yet, the possible clinical importance of these spirochetes, for which the name " Candidatus Borrelia mvumii" has been proposed, remains unresolved ( 16 , 22 , 23 ). Studies are particularly hampered by the current lack of cultivatable strains.…”
Section: Potential For Introduction or Reintroduction Into Industrialmentioning
confidence: 99%